The Influence of Internet Sharing Behavior on the Willingness of Middle-Aged and Elderly People to Buy Healthcare Products - Tang, Zhihao (Journal of Ecohumanism, 2024)
The purchasing decisions of middle-aged and elderly individuals have been deeply influenced by Internet sharing, as a means of information, dissemination and social interaction. Data was collected through a questionnaire survey, and empirical testing was conducted using a multiple linear regression model. In accordance with the study, Internet sharing behavior (comment authenticity, transmission professionalism, product homogeneity) was found to have a significant positive effect on the willingness of middle-aged and elderly people to purchase healthcare products. Based on this, management recommendations were put forward for Internet sharing platforms and content creators.